Update on knowledge of water resources of Amelia mountains (central Italy) - Di Matteo, Lucio; Dragoni, Walter; Valigi, Daniela (Italian journal of engineering geology and environment, 2009)
The Amelia Mountains, in Central Italy, are mainly made up by a set of limestone formations belonging to the Umbria-Marche, the Umbria-Romagnola Sequences and the Tuscan Units. A regional aquifer located in the Amelia Mountains drains towards the high-discharge, high-salinity Stifone-Nera Montoro springs. The piezometric data in the northern part of the system indicate an eastward flowpath, strictly related to the local geological and structural set up. During the 2006-2008 period some deep wells, located in the northern section of the structure, that provide high quality drinking water, registered a reduction in water-levels, caused by a recent decrease in rainfall and in groundwater recharge, coupled with a high pumping rate. In the same period, sulphate concentrations have progressively increased by about 35%: the sulphate increasing is probably produced by the pumping of deep bicarbonate-sulphate-alkaline-earth waters characterized by high content of sul- phates than the shallower aquifers (calcium-bicarbonate). The average water budget seems to show that the system provides at most only 15% of the total discharge of the Stifone-Nera Montoro springs. Hence the water budget indicates that the Stifone springs are fed by the Amelia Mountains besides a further 1000 km2 area. Recharge areas are to be found in the Narni Mountains, the Martani chain, the Sabini chain and probably in the lower part of the Valnerina Mountains and/or in the regional flow coming from north-eastern Umbria. At present it is not clear if the Peglia Mountain and the northern part of the Amelia Mountains feed the Stifone-Nera Montoro springs: these areas produce a maximum discharge of 0.5 m3/s.